The mangrove CO2 pump: Tidally driven pore‐water exchange. Issue 4 (21st January 2021) - Chen, Xiaogang; Santos, Isaac R.; Call, Mitchell; Reithmaier, Gloria M. S.; Maher, Damien; Holloway, Ceylena; Wadnerkar, Praktan D.; Gómez‐Álvarez, Paula; Sanders, Christian J.; Li, Ling
Abstract: Atmospheric carbon dioxide (CO2 ) is fixed by mangrove vegetation and stored in its biomass and sediments. Part of the sediment carbon can be exported to coastal waters via tidally driven pore‐water exchange. Here, we quantify pore water‐derived dissolved CO2 export using in situ, high‐resolution observations of 222 Rn and CO2 over a spring‐neap tidal cycle in a mangrove‐fringed estuary (Coffs Creek, Australia). 222 Rn‐derived pore‐water exchange rates were 11.5–34.9 cm d −1 (23.0 ± 6.7) over 30 tidal cycles. Pore‐water exchange released CO2 from intertidal sediment at rates of 61–213 (136 ± 43) mmol m −2 d −1 . This is equivalent to ~ 94% of the total CO2 input into the estuary and approximately two times of the water‐atmosphere CO2 emission. These observations reveal that tidal pumping is a major regulator of both mangrove pore‐water exchange and associated dissolved CO2 export to the ocean. Combining our estimates with literature data, a first‐order global pore water‐derived dissolved CO2 export from mangroves was estimated to be 83 ± 50 Tg C yr −1 . This is higher than an earlier estimates of global mangrove CO2 emissions to the atmosphere (34.1 ± 5.4 Tg C yr −1 ) and carbon burial in sediments (18.4–34.4 Tg C yr −1 ), implying that pore water‐derived CO2 escapes to the atmosphere within and beyond mangrove waters. Overall, CO2 ‐rich pore water seems to be a widespread, important pathway of CO2 into mangrove‐dominated estuaries and should be considered in mangrove carbon assessments in the context of global climate change and blue carbon.